Medical graduate in Brazil: integrative review (Research, Society and Development, 2022)
The analysis of the graduates evaluates the course from the point of view of those who have experienced the entire teaching and learning process. Therefore, it works as an important self-assessment tool for the educational institution. The objective of the present study is to review the profile of medical graduates trained in Brazil. This is an integrative literature review in the SciELO, LILACS and PubMed databases, using the descriptors: medical graduate and medical education. Inclusion criteria were articles published after 2001, freely available online and that addressed information on the profile of medical graduates in Brazil. A total of 9,543 articles were identified and, after evaluation, 8 articles were included. The review identified greater female participation, the participation of the graduates mainly in the public health system and completion of medical residency by the majority (70.1-96.7%). In addition, satisfaction with the quality of the course was high and a confidence rate regarding professional performance of 61.3% was shown in one of the studies. The results perhaps demonstrate the phenomenon of feminization of medicine, specialization through medical residency as a frequent objective among graduates and a greater need for new research on the subject with more standardized information to better assess the impact of the National Curricular Guidelines on the medical course.